Editorial (Bangladesh Journal of Bioethics, 2021)
With its origin in the Hippocrates Oath (5th-3rd Century BC), The Nuremberg Codes (1947), and The Declaration of Helsinki (1964), medical ethics set the rules of the professional conducts for the physicians and other medical specialists. It amounts to the deployment of bioethical concepts, values (Autonomy, Non-maleficence, Beneficence, and Justice) and methods within medical set up to suggest the day-to-day decision-making procedures by combining theory and practice. It is a multidisciplinary study as it seeks to develop a set of guidelines for moral decision-making utilizing the resources of not only medicine and biology, but also of law, philosophy, theology, and the social sciences. As the branch of Bioethics, it investigates the complex ethical problems which arise for human life and society from sophisticated medical-technological usages and biological practices. The problems specifically include the nature and distribution of treatment and medical resources, the informed consent and authority of the patient, the physician and others involved in the medical practices, the scope and limits of confidentiality, the limits of acceptable intervention and experimentation, and the propriety of research involving humans and their applications. It also deals with the questions of moral dimensions and professional responsibilities involving all forms of ‘life-related’ issues such as research involving foetal tissues, withdrawal of life-sustaining medical treatment, issues over death, prenatal diagnosis and abortion, the storage of frozen embryos. Medical ethics is intricately linked to the culture and glocal values. To emphasise such aspect, the following papers come together to enrich this volume.